Comparative Study of Land Registration Systems in Indonesia and Sweden: Review of Legal, Institutional, Procedural, and Technological Aspects - Syah, Iskandar; Abeng, Andi Tenri; Maruf, Mujahidin; Sholichin, Nurus; Parunggi, Uunk Din; Manurung, Pangihutan; Mahanani, Ariani Nastya; Puri, Widhiana Hestining; Dharma, Agustinus Dhanan Suka; Amrin, Reza Nur (Sekolah Tinggi Pertanahan Nasional, 2025)
This study examines the differences in land registration systems in Indonesia and Sweden in terms of governance and legal systems, institutions, procedures, and information systems (technology). Sweden is known to have an efficient and integrated land registration system. This study also aims to provide recommendations for the development of a land registration system in Indonesia to improve land administration services. A qualitative approach with literature studies and comparative analysis was used in this study. The results of the study show that Sweden and Indonesia implement civil law and a rights registration system. The publication system in Indonesia uses a negative system with a positive tendency, while Sweden is included in the German/Swiss Group. Land registration is carried out electronically through the Lantmäteriet page or by post with a period of 3 (three) months after acquisition. Sweden is more advanced in terms of digitalisation and blockchain development, while Indonesia still faces challenges in transparency and efficiency. This study recommends strengthening digital infrastructure and regulations, as well as implementing modern technology to improve the land registration system in Indonesia.